Pengaruh Metode Inkuiri Terbimbing terhadap Pemahaman Konsep Ikatan Kimia Siswa SMA - Larissa Cahaya Permata; Indira Cempaka Ayu; Dipa Nugraha Wijaya (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Understanding the concept of chemical bonds is a fundamental aspect in chemistry learning at the high school level. However, many students have difficulty in understanding this concept in depth. This study aims to examine the effectiveness of the guided inquiry method in improving the understanding of the concept of chemical bonds. The method used was an experiment with a control group design, where one group was taught with the guided inquiry method, while the other group used the conventional method. The results showed that students who learned with the guided inquiry method had a better understanding of the concept compared to the control group. This finding indicates that the application of the guided inquiry method can be an effective strategy in improving the quality of chemistry learning in schools.